Optimal management of esophageal cancer in Africa: A systemic review of treatment strategies. Issue 5 (6th October 2020) - Buckle, Geoffrey C.; Mahapatra, Ruchika; Mwachiro, Michael; Akoko, Larry; Mmbaga, Elia J.; White, Russell E.; Bent, Stephen; Van Loon, Katherine
Abstract: Esophageal cancer (EC) is a leading cause of cancer morbidity and mortality in Africa. Despite the high burden of disease, optimal management strategies for EC in resource‐constrained settings have yet to be established. This systematic review evaluates the literature on treatments for EC throughout Africa and compares the efficacy and safety of varying treatment strategies in this context (PROSPERO CRD42017071546). PubMed, Embase and African Index Medicus were searched for studies published on treatment strategies for EC in Africa from 1980 to 2020. Searches were supplemented by examining bibliographies of included studies and relevant conference proceedings. Methodological quality/risk of bias was assessed using the Cochrane Risk‐of‐Bias tool and the Newcastle‐Ottawa Scale. Forty‐six studies were included. Case series constituted the majority of studies: 13 were case series reporting on outcomes of esophagectomies, 17 on palliative luminal or surgical interventions, four on radiotherapy and three on concurrent chemoradiation. Nine randomized controlled trials were identified, of which four prospectively compared different treatment modalities (one investigating radiotherapy vs chemoradiation, three evaluating rigid plastic stents vs other treatments). This review summarizes the research on EC treatments in Africa published over the last four decades and outlines critical gaps in knowledge related to management in this context. Areas in need of further research include (a) evaluation of the safety and efficacy of neoadjuvant therapy in patients with locally advanced disease; (b) strategies to improve long‐term survival in patients treated with definitive chemoradiation; and (c) the comparative effectiveness of modern palliative interventions, focusing on quality of life and survival as outcome measures. Abstract : What's new? Esophageal cancer is a leading cause of cancer morbidity and mortality in Africa. This systematic review summarizes the research on esophageal cancer treatment strategies in Africa and outlines critical gaps in knowledge related to management in this context. Priority research areas include the comparative effectiveness of modern palliative interventions, the safety and efficacy of neoadjuvant therapy in patients with locally advanced disease, and strategies to improve long‐term survival in patients treated with definitive chemoradiation. The identified evidence provides a contemporary benchmark for future research and could help inform international efforts for developing resource‐stratified guidelines for cancer in Africa.